Prevalence of lymphedema symptoms across cancer diagnoses and association with depression, pain interference and health-related quality of life - Gitte Sone Larsen; Christoffer Johansen; Annika von Heymann; Bolette Skjødt Rafn (Acta Oncologica)
Background and purpose: Lymphedema is a debilitating late effect of cancer treatments, yet its prevalence beyond breast cancer remains understudied. This study examined the prevalence of lymphedema symptoms across cancer diagnoses and their association with depression, pain interference, and health-related quality of life (HRQoL).